Local Culture Based Islamic Education from a Multicultural Perspective - Dertha Mukhtar; Novi Hendri; Abdul Rahman; Soibatul Aslamiah Nasution; Yudi Gucandra (The Future of Education Journal, 2026)
This study aims to analyze the implementation of multiculturalism in local culture-based Islamic Education (PAI) at SMPN 42 Padang. Specifically, it examines the implementation of multicultural values in Islamic Education learning, the integration of local coastal culture into the curriculum, and the roles of teachers as well as the challenges encountered in implementing multicultural values in Islamic Education. The study employed a descriptive qualitative approach using field research methods. Data were collected through observations, interviews, and document analysis involving Islamic Education teachers, students, and community leaders residing near the school. The findings reveal that multicultural values, including tolerance, respect for diversity, and social solidarity, have been integrated into Islamic Education through a contextual learning approach grounded in local coastal culture. However, the implementation remains insufficiently institutionalized within the formal curriculum and continues to rely largely on individual teachers' initiatives. The study proposes a conceptual model of multicultural Islamic Education based on local culture that is contextual, culturally responsive, and relevant to the socio-cultural characteristics of coastal communities.